Pharmacokinetics, phenotype and product choice in haemophilia B: how to strike a balance?. (November 2014) - Berntorp, E.; Dolan, G.; Hermans, C.; Laffan, M.; Santagostino, E.; Tiede, A.
Summary: At the 7th Annual Congress of the European Association for Haemophilia and Allied Disorders (EAHAD) held in Brussels, Belgium, in February 2014, Pfizer sponsored a satellite symposium entitled: "Pharmacokinetics, phenotype and product choice in haemophilia B: How to strike a balance?" Co‐chaired by Cedric Hermans (Cliniques Universitaires Saint Luc, Brussels, Belgium) and Mike Laffan (Imperial College, London, UK), the symposium provided an opportunity to debate whether pharmacokinetic (PK) parameters are good surrogates for clinical efficacy for haemophilia B in clinical practice, consider the perceptions and evidence of disease severity, and examine how these considerations can inform approaches to balancing the potential risks and benefits of the currently available treatment options for haemophilia B. PK parameters are routinely measured in clinical practice and are a requirement of regulatory bodies to demonstrate the clinical efficacy of products; however, the relationship between measured PK parameters and clinical efficacy is yet to be determined, an issue that was debated by Gerry Dolan (University Hospital, Queen's Medical Centre, Nottingham, UK) and Erik Berntorp (Lund University, Malmö Centre for Thrombosis and Haemostasis, Malmö, Sweden). Elena Santagostino (Universita degli Studi di Milano, Milano, Italy) reviewed how differing perceptions on the severity of haemophilia B compared with haemophilia A may have an impact on clinical decision‐making. Finally, Andreas Tiede (Hannover Medical School, Hannover, Germany), examined the considerations for balancing the potential risks and benefits of the currently available treatment options for haemophilia B. Although the pathophysiology of haemophilia B has been widely studied and is largely understood, continued investigation and discussion around the optimal management course and appropriate therapeutic choice is warranted.